Mobilite Du Plomb Et Du Zinc Issus De Retombees Atmospheriques Dans Le Sol : Cas De La Zone Industrielle De Tiaret, Algerie - Mohamed, Benahmed; Abdelkader, Dellal; Benchaben, Hellal (European Scientific Journal, ESJ, 2016)
Study of heavy metals mobility in soil is a necessary step for making an accurate appraisal and quantitative evaluation of the extent of contamination, indeed, wet and dry atmospheric deposits, plays an important role in the cycle of semi-volatile contaminants (Vinogradova, 2000). Metallurgical industries release heavy metals into the atmosphere, these last, clump together to form fines particles suspended in the air, these metals can be transported by wind via aerosol or aqueous pathway and deposited in the soil. The main aim of this work was to study the mobility and fate of lead and zinc from atmospheric deposits in a contaminated soil from the foundry (ALFET) in the industrial zone of Tiaret (Western Algeria) and to determine the effect of physicochemical parameters of the soil on their mobility in the topsoil. The physicochemical analysis of soil samples have shown that zinc and lead levels contents in the surface layer soil (0-30cm) vary depending on the pH, total limestone (CaCO3). The obtained results clearly show the major effect of soil texture, the fine fraction (clay and sand).